The Association of Serum Electrolytes with Disease Severity and Obstetric Complications in Pregnant Women with COVID-19: a Prospective Cohort Study from a Tertiary Reference Center - Tanacan, Atakan; Erol, Seyit Ahmet; Anuk, Ali Taner; Yetiskin, Fatma Didem Yucel; Tokalioglu, Eda Ozden; Sahin, Selin; Unlu, Serpil; Keskin, Huseyin Levent; Surel, Aziz Ahmet; Tekin, Ozlem Moraloglu; Sahin, Dilek (Geburtshilfe und Frauenheilkunde, 2022)
Introduction To evaluate the association of serum electrolytes with disease severity and obstetric complications in pregnant women with Coronavirus disease 2019 (COVID-19).Materials and Methods This prospective cohort study was conducted on pregnant women with confirmed COVID-19. Study population was divided into two groups: 1) Mild COVID-19 group (n = 811) and 2) Moderate/severe COVID-19 group (n = 52). Demographic features, clinical characteristics, obstetric complications, and serum electrolytes were compared between the groups. Afterward, a correlation analysis was performed to investigate the association between serum electrolyte disturbances with COVID-19 severity and obstetric complications.Results Highest serum sodium, hypernatremia, potassium replacement, hypopotassemia, hyperchloremia, initial serum magnesium, hypermagnesemia, and hypocalcemia were significantly higher in the moderate/severe COVID-19 group. The lowest serum sodium, lowest serum potassium, and initial serum calcium were significantly higher in the mild COVID-19 group (p < 0.05). Statistically significant positive weak correlations were found between hypernatremia, hypopotassemia, hyperchloremia, hypermagnesemia, hypocalcemia and COVID-19 severity (r values were 0.27, 0.20, 0.12, 0.18 and 0.12, p values were < 0.001, < 0.001, 0.02, 0.03 and 0.03, respectively). Furthermore, statistically significant positive weak correlations were found between hypopotassemia, hypochloremia, hypermagnesemia, and obstetric complications (r values were 0.10, 0.10, and 0.28, p values were 0.004, 0.03, and 0.001, respectively). A statistically significant negative weak correlation was found between hypomagnesemia and obstetric complications (r = − 0.23 and p = 0.01, respectively).Conclusion Electrolyte disturbances in pregnant women with COVID-19 seem to be associated with disease severity and obstetric complications.
Keywords: COVID-19; disease severity; electrolytes; obstetric complications; pregnancy